2005
DOI: 10.1177/009102600503400101
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Strategic HRM Effectiveness: A Case Study of an Australian Public Sector Agency during Commercialization

Abstract: This study examines the effectiveness of the human resource management (HRM) function of a public sector entity as it became corporatized. There has been little empirical research regarding the effectiveness of the people management functions within the Australian public sector as these entities went through a period of transition to commercialization. A questionnaire obtaining perceptions on different aspects of HR effectiveness, both before and after corporatization, was administered to a sample (N = 122) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Furthermore, it was supported by Guest (2001), employer reports on the HRM effectiveness from their perspective as a manager, not from their experience of the actual practices-they are not the consumers of HRM, the employee are. Unlike many studies of HRM which are based on data supplied solely by HR managers, studies adopting the multiple constituency perspective necessarily include assessments of HRM effectiveness by non-HRM staff (Geare Edgar, & Deng, 2006;Han, Chou, Chao, & Wright, 2006;Kane, Crawford, & Grant, 1999;Mitsuhashi, Park, Wight, & Chua, 2000;Teo & Crawford, 2005;Wright, McMahan, Snell, & Gerhart, 2001). Therefore, collecting data from HR manager as well as line manager is likely to enhance the reliability of findings reported in studies on HRM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, it was supported by Guest (2001), employer reports on the HRM effectiveness from their perspective as a manager, not from their experience of the actual practices-they are not the consumers of HRM, the employee are. Unlike many studies of HRM which are based on data supplied solely by HR managers, studies adopting the multiple constituency perspective necessarily include assessments of HRM effectiveness by non-HRM staff (Geare Edgar, & Deng, 2006;Han, Chou, Chao, & Wright, 2006;Kane, Crawford, & Grant, 1999;Mitsuhashi, Park, Wight, & Chua, 2000;Teo & Crawford, 2005;Wright, McMahan, Snell, & Gerhart, 2001). Therefore, collecting data from HR manager as well as line manager is likely to enhance the reliability of findings reported in studies on HRM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most scales used by scholars (Budhwar and Sparrow 1997;Huselid, Jackson and Schuler 1997;Teo 2000;Green, Cindy, Whitten and Medlin 2006) focus on SHRM narrowly, taking a rather limited view of SHRM. Scales used in SHRM studies (Chang and Huang 2005;Sheehan 2005;Teo and Crawford 2005;Ozcelik and Aydýnlý 2006) have primarily emphasized fit between HRM function and corporate strategy while ignoring other dimensions of SHRM (e.g. fit between HRM and other functional areas or fit among HR subfunctions).…”
Section: Introductionmentioning
confidence: 99%
“…Organization development (OD) is used increasingly in strategic change initiatives in public sector organizations (Ferlie et al, 1996;Robertson and Seneviratne, 1995;Patchett, 2005;Teo and Crawford, 2005). The reasons for strategic change in the public sector are mostly found in abrupt and predominantly exogenous jolts such as changing policies or legislation, technological change, top management replacements or reorganizations such as the joining together or the breaking up of public agencies.…”
Section: Introductionmentioning
confidence: 99%
“…However, comparisons between decision-making in public and in private organizations have revealed that successful implementation in the public sector also requires a bottom-up approach with some degree of employee participation (Rodrigues and Hickson, 1995;Hickson et al, 2003). This explains the growing interest in OD concepts and methods in the public sector (Robertson and Seneviratne, 1995;Ferlie et al, 1996;Patchett, 2005;Teo and Crawford, 2005). Nevertheless, the introduction of OD in organizations that are accustomed to centralized control and bureaucratic and political working conditions may clash with the prevailing organization culture or can even be perceived as undermining the public administration work ethos (Barnhart, 1997;O'Brien, 2002).…”
Section: Introductionmentioning
confidence: 99%